Multicentric pheochromocytoma and involvement of the inferior vena cava - Lucon, Antonio Marmo; Falci Júnior, Renato; Praxedes, José Nery; Machado, Marcel Cerqueira Cesar; Saldanha, Luis Balthazar; Machado, Marcelo Marcondes; Arap, Sami (São Paulo Medical Journal, 2001)
CONTEXT: Extension of pheochromocytomas to the inferior vena cava is rare. Multicentric tumors are rare as well, being present in up to 10% of cases. Surgery is the treatment of choice because of the longterm survival free of disease. DESIGN: Case report. CASE REPORT: We report on a case of right adrenal pheochromocytoma with extension to the supra-diaphragmatic vena cava, which underwent surgical excision through thoracophrenic laparotomy without the need for cardiopulmonary bypass. In a 6-year follow-up, another pheochromocytoma was found in the infra-renal Zuckerkandl’s organ. Complete surgical excision of the tumor was performed by a median laparotomy and complete retroperitoneal dissection. In both cases, the total removal of the pheochromocytoma has been guaranteed by having margins free of tumor and a normal post-operative level of catecholamines. The pathological study revealed a malignant pheochromocytoma with margins free of neoplasia in both specimens.